Pathophysiology, Symptoms and Evolving Treatment for Colonic Diverticular Disease: A Review - Neelottama Kushwaha; Swatantra K.S. Kushwaha (Research Center for Rational Use of Drugs (RCRUD), 2022)
The review on diverticulitis disease, is the most prevalent non-cancerous pathology of the colon is diverticular disease and diverticulitis. It has long been thought to be a disease of the elderly, linked to cultural and dietary patterns. Our understanding of this condition, as well as the therapy protocols, has progressed. To give an updated assessment of the epidemiology, pathophysiology, and classification of diverticulitis, as well as to highlight developments in medicinal and surgical management. Treatment of Diverticular Disease represented an important challenge in clinical practice, especially concerning the management of symptomatic uncomplicated diverticular disease (SUDD) and the primary and secondary prevention of acute diverticular disease (AD). Antibiotics and supportive treatments are the mainstays of non-operative treatment, while antibiotics may be skipped in moderate cases. Acute surgery is required for the most severe and refractory cases, whereas elective resections should be considered for chronic, smoldering, or recurrent forms, as well as their associated complications (stricture, fistula, etc.) and patients with factors that are highly predictive of recurrent attacks. Diverticulitis isn't just a condition that affects the elderly. Our growing understanding of diverticulitis as a clinical entity has resulted in a more nuanced approach to its medicinal and surgical therapy. For more than 70% of patients, non-surgical care is still the best option. In the acute, chronic, or elective-prophylactic environment, a segmental colectomy remains the most effective surgical treatment for those with non-relenting, persistent, or recurrent symptoms, as well as those with severe disease and sequelae.